In situ formation of DNA-templated copper nanoparticles as fluorescent indicator for hydroxylamine detection. Issue 45 (20th August 2019) - Song, Quanwei; Chen, Changzhao; Yu, Wenhe; Yang, Lixia; Zhang, Kunfeng; Zheng, Jin; Du, Xianyuan; Chen, Hongkun
Abstract : Herein, we develop a facile method for selective and sensitive detection of hydroxylamine (HA) based on the in situ formation of DNA templated copper nanoparticles (DNA-CuNPs) as fluorescent probes. Abstract : Herein, we develop a facile method for selective and sensitive detection of hydroxylamine (HA) based on the in situ formation of DNA templated copper nanoparticles (DNA-CuNPs) as fluorescent probes. It is firstly found that HA as a reducing agent can play a key role in the in situ formation of fluorescent DNA-CuNPs. This special optical property of DNA-CuNPs with ( λ ex = 340 nm, λ em = 588 nm) with a mega-Stokes shifting (248 nm) makes it applicable for the turn-on detection of HA. In addition, this fluorescent method has several advantages such as being simple, rapid, and environmentally friendly, because it avoids the traditional organic dye molecules and complex procedures. Under optimized conditions, this platform achieves a fluorescent response for HA with a detection limit of 0.022 mM. Especially, successful detection capability in tap waters and ground waters exhibits its potential to be general method.